2014
DOI: 10.4236/oalib.1100735
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Petroleum Compound Using Pseudomonas aeruginosa

Abstract: The present study was conducted to determine the biodegradation of petrol by Pseudomonas aeruginosa isolated from petrol contaminated soil. The isolated strain was able to grow in minimal broth along with 2.5%, 5%, 7.5% and 10% concentrations of petrol which indicated the capability of the organism in degrading petrol and utilizing it as a source for growth. The isolated strain's efficiency was determined by analyzing the parameters pH, optical density and CO2 released during petrol degradation. High Performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…Mikroba yang dapat digunakan salah satunya yakni mikroba indigen yang merupakan biota lokal berasal dari lingkungan yang tercemar. Studi tentang biodegradasi hidrokarbon memanfaatkan bakteri indigen telah banyak dilakukan salah satunya di India menggunakan Pseudomonas aeruginosa [4]. Bakteri indigen memiliki kemampuan mendegradasi senyawa hidrokarbon untuk keperluan metabolismenya dan sudah teradaptasi dengan berbagai faktor lingkungan di habitat asalnya.…”
Section: Pendahuluanunclassified
“…Mikroba yang dapat digunakan salah satunya yakni mikroba indigen yang merupakan biota lokal berasal dari lingkungan yang tercemar. Studi tentang biodegradasi hidrokarbon memanfaatkan bakteri indigen telah banyak dilakukan salah satunya di India menggunakan Pseudomonas aeruginosa [4]. Bakteri indigen memiliki kemampuan mendegradasi senyawa hidrokarbon untuk keperluan metabolismenya dan sudah teradaptasi dengan berbagai faktor lingkungan di habitat asalnya.…”
Section: Pendahuluanunclassified
“…The PAHs are dangerous and persistent FO6 compounds that can put people's health at risk and cause harm to the environment. Alkenes, in general, have toxic, carcinogenic, and mutagenic properties and represent a significant danger to health and the environment [6]. Inoculation of the growth medium: One gram of contaminated soil was mixed with 9 mL of sodium salt solution (NaCl 1%) to obtain a 10 −1 dilution, and it was vortex shaken for 1 min.…”
Section: Fuel Oilmentioning
confidence: 99%
“…In this process, FO6 is a rich source of organic compounds that serve as nutrients for the growth and development of P. aeruginosa. Darsa and Thatheyus [6] reported that P. aeruginosa exhibits an excellent ability to degrade n-hexadecane (C 16 H 34 ). Das and Chandran [25] reported that P. aeruginosa in its catabolic cycle produces a biosurfactant called rhamnolipid, an enzyme considered biosurfactant that allows it to take the carbon from the hydrocarbon.…”
Section: Assessing Bioremediationmentioning
confidence: 99%
See 2 more Smart Citations